2021
DOI: 10.3390/s21103527
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Sensor-Based Step Length Estimation Model by Means of Principal Component Analysis

Abstract: Inertial sensor-based step length estimation has become increasingly important with the emergence of pedestrian-dead-reckoning-based (PDR-based) indoor positioning. So far, many refined step length estimation models have been proposed to overcome the inaccuracy in estimating distance walked. Both the kinematics associated with the human body during walking and actual step lengths are rarely used in their derivation. Our paper presents a new step length estimation model that utilizes acceleration magnitude. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…is used to estimate the length of each step taken by the user [43], [44]. Weinberg formula is an empirical relation that is commonly utilized in PDR systems to estimate the step length with respect to the user's acceleration.…”
Section: ) Distance Estimationmentioning
confidence: 99%
“…is used to estimate the length of each step taken by the user [43], [44]. Weinberg formula is an empirical relation that is commonly utilized in PDR systems to estimate the step length with respect to the user's acceleration.…”
Section: ) Distance Estimationmentioning
confidence: 99%
“…In contrast, Weinberg [ 55 ] used the difference between maximum and minimum acceleration values within a step as the basis, whereas Kim et al [ 56 ] utilized the mean absolute acceleration value in the walking direction within the step. Vezočnik et al [ 57 ] based their model on the difference between maximum and minimum acceleration magnitude values within the step. Guo et al [ 58 ] and Bylemans et al [ 31 ] extended the model proposed by Kim et al [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…In one of our previous studies, we conducted an in-depth analysis and comparison of representative step length estimation models and demonstrated that the performances of certain models change under different evaluation protocols when smartphone placements and walking speeds vary in trials [ 48 ]. Moreover, authors also rarely consider the kinematics of different body segments during walking and step lengths in the derivation process of the model [ 57 ]. Specifically, identifying similar characteristics related to the movement of anatomical landmarks by means of the kinematics of the human body during walking does not often lay the groundwork for a new model, as it did in our previous study in which we proposed a step length estimation model based on the difference between maximum and minimum acceleration magnitude values within the step [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations